Legal Protection for Child Kidnapping Victims: Case Study in Gianyar District Court - Suartana, Komang; Wirya Darma, I Made (Kertha Patrika; Vol 42 No 3 (2020)DO - 10.24843/KP.2020.v42.i03.p07, 2020)
This article aims to analyze how the crime of child kidnapping is covered in the Indonesian Criminal Code and the type of sanctions that can be imposed on the perpetrator of the crime of child kidnapping. It is a legal research that uses statutory, conceptual, and case approaches in discussing the legal protection of child kidnapping victims. In order to illustrate how the law that protects the victim of child kidnapping is applied by the court, it presents a case study at the Gianyar District Court that investigated a criminal offense of child kidnapping in 2018. The results reveal that the Indonesian Criminal Code classifies child kidnapping as a crime that is punishable as stipulated in Article 330 of the Code. In a more specific context, Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments to Law Number 22 of 2003 concerning Child Protection includes child kidnapping as a case that needs to be given special protection  A case study regarding the imposing of sanctions on the perpetrator of child kidnapping can be seen in a criminal case before the District Court of Gianyar in 2018. In the judgment, the panel of judges imposing a sentence against the defendant in the form of imprisonment of 8 (eight) years in prison and a fine of Rp. 60,000,000 (sixty million rupiah) subsidiary 6 (six) months in prison;